2020
DOI: 10.3390/ijerph17176224
|View full text |Cite
|
Sign up to set email alerts
|

The 4 U’s Rule of Fibromyalgia: A Proposed Model for Fatigue in a Sample of Women with Fibromyalgia: A Qualitative Study

Abstract: Although fatigue usually goes unnoticed, it is a symptom that poses great challenges to patients with fibromyalgia and is a strong limitation. The aim of this study is to identify and describe the variables involved in fatigue in nine different situations of the Goal Pursuit Questionnaire (GPQ) that may occur in the daily lives of women with fibromyalgia, according to an ABC (Antecedents–Behaviors–Consequences) model. This study followed a qualitative descriptive research method and a deductive–inductive hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…The goal of this study has been to develop and validate the adaptation of the Spanish version of the GPQ [20] in relation to fatigue, an essential and forgotten symptom of FM [24]. The…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The goal of this study has been to develop and validate the adaptation of the Spanish version of the GPQ [20] in relation to fatigue, an essential and forgotten symptom of FM [24]. The…”
Section: Discussionmentioning
confidence: 99%
“…The goal of this study has been to develop and validate the adaptation of the Spanish version of the GPQ [ 20 ] in relation to fatigue, an essential and forgotten symptom of FM [ 24 ]. The analyses concerning the internal structure of the GPQ-F showed that this version is consistent with the original scale and reaches comparable psychometric standards.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With a view to future research, it would be necessary to examine the consistency of the clusters identified in other samples of FM patients, the confirmation of the optimal number of clusters via complementary statistical methods (e.g., latent profile analysis), the replicability of findings using revised versions of the self-reports (e.g., FIQ-revised), as well as the stability along the time of the clusters. Likewise, and given the key role of fatigue in FM patients (Velasco-Furlong et al, 2020), it would be of great interest to examine whether the dimensionality of fatigue is also reflected in the establishment of clusters. It would also be of remarkable clinical utility to establish the predictive value of the classification generated by analyzing the differential response of each subgroup to CBT.…”
Section: Discussionmentioning
confidence: 99%
“…Fibromyalgia (FM) is a complex syndrome characterized by frequent chronic musculoskeletal pain and widespread sensitivity, which is often accompanied by symptoms such as extreme fatigue [ 1 ], cognitive decline [ 2 ], sleep disturbances [ 3 ], and psychological and affective disorders [ 4 ], among others [ 5 , 6 ]. These symptoms cause significant functional impairment [ 7 ] and higher levels of physical deterioration [ 8 ].…”
Section: Introductionmentioning
confidence: 99%